The Main Dramatic Features of Melodrama: A Dramatic Study of Maria Martin and Sweeney Todd And Their Traces In Modern Soap Operas - Hamadi, Lutfi (European Scientific Journal, ESJ, 2017)
This paper attempts an exploration of the prosperity of melodrama in the nineteenth century with its literary shortcomings in comparison with more serious and deeper plays before and after that era. Shedding light on the political, social, and economic changes that took place in Europe in general and in England in particular, this study tries to show how melodrama reflected these changes and represented the new rising middle class with all their values, beliefs, and interests. In addition, the paper shows similarities between melodrama and modern soap operas and movies, with their artificially fabricated plots and endings, unconvincing characters, and irrational incidents and coincidences. For this purpose, the study will trace the main dramatic features of melodrama and mark them out in two of the most notable melodramas of that period, namely Maria Martin and Sweeney Todd, which were adapted and produced cinematically. The paper will conclude how changes in different aspects of society are definitely reflected on the literary works during a certain period of time. The methodology will include an historical overview, shedding light on the changes that took place in England in the 19th century, comparing and contrasting melodramas and other more important literary forms, together with the two plays to be studied as examples. To achieve credibility, the paper will refer to works by remarkable thinkers and critics in the field, illustrate by using quotes from both plays, and interpret and analyze their function and importance.